Increased sympathetic and decreased parasympathetic cardiovascular modulation in normal humans with acute sleep deprivation - Zhong, Xu; Hilton, H. John; Gates, Gregory J; Jelic, Sanja; Stern, Yaakov; Bartels, Matthew N; DeMeersman, Ronald E; Basner, Robert C (Journal of applied physiology (1985), 2005)
Departments of 1 Medicine, 2 Neurology, and 3 Rehabilitation Medicine, Columbia University College of Physicians and Surgeons, and 4 Department of Biobehavioral Sciences, Columbia University Teachers College, New York, New York Submitted 18 June 2004 ; accepted in final form 15 February 2005 Cardiovascular autonomic modulation during 36 h of total sleep deprivation (SD) was assessed in 18 normal subjects (16 men, 2 women, 26.0 ± 4.6 yr old). ECG and continuous blood pressure (BP) from radial artery tonometry were obtained at 2100 on the first study night (baseline) and every subsequent 12 h of SD. Each measurement period included resting supine, seated, and seated performing computerized tasks and measured vigilance and executive function. Subjects were not supine in the periods between measurements. Spectral analysis of heart rate variability (HRV) and BP variability (BPV) was computed for cardiac parasympathetic modulation [high-frequency power (HF)], sympathetic modulation [low-frequency power (LF)], sympathovagal balance (LF/HF power of R-R variability), and BPV sympathetic modulation (at LF). All spectral data were expressed in normalized units [(total power of the components/total power-very LF) x 100]. Spontaneous baroreflex sensitivity (BRS), based on systolic BP and pulse interval powers, was also measured. Supine and sitting, BPV LF was significantly increased from baseline at 12, 24, and 36 h of SD. Sitting, HRV LF was increased at 12 and 24 h of SD, HRV HF was decreased at 12 h SD, and HRV LF/HF power of R-R variability was increased at 12 h of SD. BRS was decreased at 24 h of SD supine and seated. During the simple reaction time task (vigilance testing), the significantly increased sympathetic and decreased parasympathetic cardiac modulation and BRS extended through 36 h of SD. In summary, acute SD was associated with increased sympathetic and decreased parasympathetic cardiovascular modulation and decreased BRS, most consistently in the seated position and during simple reaction-time testing. baroreflex; sympathovagal balance Address for reprint requests and other correspondence: R. C. Basner, Division of Pulmonary, Allergy and Critical Care, Columbia Univ. College of Physicians & Surgeons, 622 West 168th St., VC 12-206, New York, NY 10032